Electrocatalysts: Cu, N‐Codoped Carbon Nanodisks with Biomimic Stomata‐Like Interconnected Hierarchical Porous Topology as Efficient Electrocatalyst for Oxygen Reduction Reaction (Small 43/2019). Issue 43 (22nd October 2019) - Wang, Tao; Yang, Rui; Shi, Naien; Yang, Jing; Yan, Hongyu; Wang, Junyi; Ding, Zhen; Huang, Wei; Luo, Qing; Lin, Yue; Gao, Jian; Han, Min
Abstract : Inspired by the stomata of plant leaves, Naien Shi, Yue Lin, Min Han, and co‐workers fabricate 2D Cu‐N‐C nanodisks with stomata‐like interconnected hierarchical porous topology by etching Cu‐tetrapyridylporphyrin (TPyP)‐metal–organic frameworks carbonization product (Cu@Cu‐N‐C) in article number 1902410 . Such nanodiscs manifest superior oxygen reduction reaction performance, outperforming Cu@Cu‐N‐C, Pt/C, and most reported M‐N‐C catalysts. This work may promote the optimization and application of 2D M‐N‐C nanostructures in gas‐involved energy electrocatalysis fields.